(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Soursop leaf, Annona muricatais a type of plant that contains active compounds, one of which is flavonoids, which can reduce cholesterol levels. This study aims to determine the dose of soursop leaf extract, A. muricatathe optimum for adding to bete-bete fish as feed in mangrove crab cultivation. This research was conducted at the Takalar Brackish Water Aquaculture Fishery Center, South Sulawesi Province for 28 days. The test animals used were mangrove crabs, Scylla olivacea60 males with average weight158.98±15.91g which were kept in the crab house measuring length, width, and height of 35 x 19 x 17 cm each filled with 1 crab per container. This study consisted of 4 treatments and 3 replications each with the addition of soursop leaf extract doses of 0 (control treatment/A), 200 ppm (B), 400 ppm (C), and 600 ppm (C) for the bete-bete fish. Data management uses ANOVA and W-Tuckey test. The results showed that the higher the dose of soursop leaf extract, A. muricata showed a significant effect on survival, cholesterol levels, hemolymph triglyceride levels, protein, fat and carbohydrate levels, and did not significantly differ on daily growth, absolute growth and feed efficiency. Based on this study it was concluded that the best additional dose of soursop leaf extract, A. muricata, was 400 ppm.